LIFE HISTORY OF ATTACUS ATLAS LINN. (SATURNIIDAE: LEPIDOPTERA) ON SAPIUM INSEGNE BENTH. FROM WESTERN GHATS, MAHARASHTRA - G. P. BHAWANE; A. B. MAMLAYYA; Y. J. KOLI; Y. A. PHONDE; S. R. ALAND; S. M. GAIKWAD (The Bioscan, 2011)
Attacus atlas is the largest and beautiful among Saturniid found throughout India and also in Western Ghats region of Kolhapur district, Maharashtra, India. The rearing of the saturniid Attacus atlas was done on Sapium insegne under laboratory conditions. It completes its one generation within 78 to 100 days with the duration of egg, larval and pupal stages as 8-10, 32-45, 38-45 days respectively. Laboratory rearing and the biology of A. atlas indicated that two generations are possible in a year and pupae enter in diapause after second generation in the months of December/ January. Indoor rearing is possible on large scale for commercial silk production by using Sapium insegne as a food plant which occurred plenty throughout the forest area of Kolhapur district.